'Notebook' Lyricism of zygmunt Krasiński in the Context of the Poem "Bóg mi odmówił tej anielskiej miary" ("God Has Denided Me the Angelic Measure") - Szczeglacka-Pawłowska, Ewa (Colloquia Litteraria, 2018)
The article is an interpretation of Krasiński’s poem with respect to ‘notebook romanticism’ category. The author analyses the poem in the light of Krasiński’s literary creation process, which is preserved in the Romantic art of editing.